Genealogi Liberalisasi Pemikiran Islam - Hamid Fahmy (Ulumuna, 2009)
Liberalization of islamic thought is often related to or claimed as renewal of islamic thought (tajdid), yet the term ‘liberal’ itself has no root in islamic intellectual tradition, let alone the concepts offered by this movement. The genealogy of thought that underlines this movement is traceable from the trend of postmodernism and the remnant of modernism in the West. In fact, the shift from modernism to postmodernism in the West brought about the approaches of social and human sciences studies, including religious studies. Such doctrines that came along with the trend of thought in Western postmodernism as relativism, nihilism, pluralism, equality, feminism, democratization in all respect are doctrines that played pivotal role in liberalization of religious thought in the West. Now, those doctrines are playing in the mind of the exponent of liberalization of Islamic thought with almost the same rationale with the program of secularization.